Slurry spray coating of carbon steel for use in oxidizing and humid environments. Issue 7 (May 2018) - Nguyen, Minh Dat; Bang, Jung Won; Kim, Young Hee; Bin, An Su; Hwang, Kyu Hong; Pham, Vuong-Hung; Kwon, Woo-Teck
Abstract: Barrier coatings can be used to prevent corrosion of steel in high-temperature applications with oxidizing and humid environments. This study describes the development of a high-performance environmental barrier coating for steel using a slurry spraying process. In this process, a solution or suspension is deposited onto a substrate using air spraying. Parameters such as the pre-treatment of the steel substrates, filler systems, filler volume, and coating thickness were varied to optimize the coatings. The resulting coatings were investigated using thermogravimetric analysis, scanning electron microscopy with X-ray micro analysis, and X-ray diffraction to clarify the possible protective and bonding mechanisms. Finally, oxidation, thermal shock resistance, and humidity resistance tests were performed to evaluate the performance of the developed coating under harsh environments simulating real applications. It was concluded that the developed coatings were appropriate for protecting steels such as those used in steam boiler tube systems in waste incineration plants.